2020
DOI: 10.3390/met10121634
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Visibility Limit of Pores in Metal Powder for Additive Manufacturing

Abstract: The quality of additively manufactured (AM) parts is determined by the applied process parameters used and the properties of the feedstock powder. The influence of inner gas pores in feedstock particles on the final AM product is a phenomenon which is difficult to investigate since very few non-destructive measurement techniques are accurate enough to resolve the micropores. 3D X-ray computed tomography (XCT) is increasingly applied during the process chain of AM parts as a non-destructive monitoring and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A review paper on the subject is also published in this Special Issue [4]. Moreover, advanced imaging techniques, in particular laboratory and synchrotron X-ray computed tomography, are used to disclose the defects generated by AM processes and some strategies for their mitigation [5][6][7].…”
Section: Characterization and Process Monitoringmentioning
confidence: 99%
“…A review paper on the subject is also published in this Special Issue [4]. Moreover, advanced imaging techniques, in particular laboratory and synchrotron X-ray computed tomography, are used to disclose the defects generated by AM processes and some strategies for their mitigation [5][6][7].…”
Section: Characterization and Process Monitoringmentioning
confidence: 99%
“…XCT is timedemanding and only works with small amounts of feedstock powder, usually a few milligrams. For varied pore and particle dimensions, 3D digital radiographs were simulated to estimate the visibility of pores inside metallic particles; a validation experiment was carried out [17]; it was shown numerically and experimentally that typical gas pores in metallic microparticles larger than a particular size (here: 3 to 4.4 μm for the selected x-ray setup) could be successfully recognized by digital radiographs [17]. About twenty years ago, gamma radiography was developed [18] as an addition to x-ray radiography to offer a method of evaluating welded assemblies, castings, and other engineering structures in metal material to check the internal defects like cracks and blowholes by iridium-192; also, the experiences have shown that the radiation from radon or radium has high penetrating, making it particularly ideal for evaluating and examine thick casting of copper alloys or steel [19].…”
Section: Introductionmentioning
confidence: 99%